Cloning of firefly luciferase cDNA and the expression of active luciferase in Escherichia coli. - de Wet, J R (1985)
A cDNA library was constructed from firefly (Photinus pyralis) lantern poly(A)+ RNA, using the Escherichia coli expression vector lambda gt11. The library was screened with anti-P. pyralis luciferase (Photinus luciferin:oxygen 4-oxidoreductase, EC 1.13.12.7) antibody, and several cDNA clones expressing luciferase antigens were isolated. One clone, lambda Luc1, contained 1.5 kilobase pairs of cDNA that hybridized to a 1.9- to 2.0-kilobase band on a nitrocellulose blot of electrophoretically fractionated lantern RNA. Hybridization of the cloned cDNA to lantern poly(A)+ RNA selected an RNA that directed the in vitro synthesis of a single polypeptide. This polypeptide comigrated with luciferase on NaDodSO4/PAGE and produced bioluminescence upon the addition of luciferin and ATP. A 1.8-kilobase-pair cDNA was isolated by probing the firefly cDNA library with the cDNA from lambda Luc1. This cDNA contained sufficient coding information to direct the synthesis of active firefly luciferase in E. coli.